If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x-4=3(7x-8)
We move all terms to the left:
11x-4-(3(7x-8))=0
We calculate terms in parentheses: -(3(7x-8)), so:We get rid of parentheses
3(7x-8)
We multiply parentheses
21x-24
Back to the equation:
-(21x-24)
11x-21x+24-4=0
We add all the numbers together, and all the variables
-10x+20=0
We move all terms containing x to the left, all other terms to the right
-10x=-20
x=-20/-10
x=+2
| 6a-48+3a=6a | | 6a-49+3a=6a | | 125=5(1-3x) | | 6(x-1)=2x-8 | | 3x-49+2x-21=x+46 | | 14-3x=22 | | x-4(x+1)=-3 | | A=x(204450000) | | 7-(2u+4)=7u-5 | | -2.2-6x=11 | | 4x+4(-4x+2)=-88 | | 5x-3=10x-14 | | 2y+4/5=2 | | t-15+t-14=t+27 | | -191=-5(6-3n)+8n | | 3x/2=x+7 | | 4(u+5)-7u=1 | | 0=18-3x | | 17w-25+7w-23=17w+6 | | 5(2x-1)=5(3x+4) | | 22=2-x | | x^2=64/255 | | 9-8n+4n=18-73 | | 17x+11=19x+40 | | 1.25x15=18.75 | | 52/9=-10/3m+7/6m | | 3(w-4)^2=84 | | -15/4=k-3/2-11/4 | | 3(x7)=12x-15 | | -85/36=1/3b-7/4b | | 2x^2-7x+31=0 | | x-8=6(x-2) |